Peri-Implant bone response around porous-surface dental implants: A preclinical meta-analysis - Abeer Ahmed; Abdulaziz Al-Rasheed; Mohammed Badwelan; Hamdan S Alghamdi (Saudi Dental Journal)
Introduction: This meta-analysis of relevant animal studies was conducted to assess whether the use of porous-surface implants improves osseointegration compared to the use of non-porous-surface implants. Material and methods: An electronic search of PubMed (MEDLINE) resulted in the selection of ten animal studies (out of 865 publications) for characterization and quality assessment. Risk of bias assessment indicated poor reporting for the majority of studies. The results for bone-implant contact (BIC%) and peri-implant bone formation (BF%) were extracted from the eligible studies and used for the meta-analysis. Data for porous-surface implants were compared to those for non-porous-surface implants, which were considered as the controls. Results: The random-effects meta-analysis showed that the use of porous-surface implants did not significantly increase overall BIC% (mean difference or MD: 3.63%; 95% confidence interval or 95% CI: −1.66 to 8.91; p = 0.18), whereas it significantly increased overall BF% (MD: 5.43%; CI: 2.20 to 8.67; p = 0.001), as compared to the controls. Conclusion: Porous-surface implants promote osseointegration with increase in BF%. However, their use shows no significant effect on BIC%. Further preclinical and clinical investigations are required to find conclusive evidence on the effect of porous-surface implants.